1997
DOI: 10.1152/ajpregu.1997.273.1.r407
|View full text |Cite
|
Sign up to set email alerts
|

The vagus nerve in the thermoregulatory response to systemic inflammation

Abstract: Experimentally, systemic inflammation induced by a bolus intravenous injection of lipopolysaccharide (LPS) may be accompanied by three different thermoregulatory responses: monophasic fever (the typical response to low doses of LPS), biphasic fever (medium doses), and hypothermia (high doses). In our recent study [Romanovsky, A. A., V. A. Kulchitsky, C. T. Simons, N. Sugimoto, and M. Székely. Am. J. Physiol. (Regulatory Integrative Comp. Physiol.). In press], monophasic fever did not occur in subdiaphragmatica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
123
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(134 citation statements)
references
References 11 publications
11
123
0
Order By: Relevance
“…17,19 This was supported by data obtained on rats pretreated with small i.p. doses of capsaicin: the febrile response was suppressed, presumably due to widePerivagal capsaicin and fever 263 spread damage of C-fibers of the abdominal cavity.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…17,19 This was supported by data obtained on rats pretreated with small i.p. doses of capsaicin: the febrile response was suppressed, presumably due to widePerivagal capsaicin and fever 263 spread damage of C-fibers of the abdominal cavity.…”
Section: Discussionsupporting
confidence: 55%
“…doses of bacterial LPS in rats (although fevers to large i.v. doses of LPS were not influenced), 17,18 while other authors found much stronger inhibition of fever by vagotomy in a different species. 19 The effects were explained by destruction of vagal afferent fibers that were presumed to carry information mainly from the liver, at which place LPS is preferentially detoxified.…”
Section: Introductionmentioning
confidence: 73%
“…This interpretation is supported by the finding that in fluoxetine-treated rats, LPS-induced hyperthermia was facilitated in time and more pronounced during the initial few hours, but not at the later time points. LPS-induced hypothermia involves reduced thermogenesis by macrophagedependent , nonvagal (Romanovsky et al 1997) peripheral (Saper 1998) mechanisms. Several mediators have been proposed to be involved in LPSinduced hypothermia, including prostaglandins Wang et al 1997), leukotriens (Paul et al 1999), IL-10 (Leon et al 1999), TNF␣ and vasopressin Saper 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the first question, it is possible that LPS when injected at high doses may leave the compartment (e.g., via circulation) and provoke systemic or local responses in other tissues. It must be remembered that in vagotomized rats the febrile effect of intraperitoneal LPS, mainly at high doses, is not always blocked (29) and that the pyrogen may induce fever when injected in other compartments of vagotomized animals. Using the Limulus amebocyte lysate assay we recently obtained evidence that, with the exception of few animals treated with a high LPS dose, LPS does not appear in the circulation of guinea pigs after its injection into the subcutaneous chamber.…”
Section: Afferent Neural Signals and Fever: A Role For Cutaneous Sensmentioning
confidence: 99%
“…Even the LPS-induced expression of the c-Fos and IL-1ß genes within the brain is depressed in vagotomized rats or mice (26,27). Suppression of LPS fever after vagotomy has been reported for guinea pigs (3,28) and rats (29), but this phenomenon seems to depend on the injected dose of LPS (29) and on the route of LPS administration (28). One study even reported that subdiaphragmatic vagotomy failed to cause a significant suppression of fever (30).…”
mentioning
confidence: 99%